Information Support of Oraganization of Communication Between Citizens and Archival Institutions - Markovets, O.; Tereshchuk, V.; Kravets, R.; Talanchuk, D. (Visnyk Kharkivsʹkoï derz͡h︡avnoï akademiï kulʹtury, 2023)
The relevance of the article. The Internet is a powerful tool for finding and providing information. In modern conditions, one of the most important elements of the functioning of the Internet is a website, which ensures the proper process of communication between all participants of the virtual space. As a result, the development of a website on the Internet will allow the use of modern technologies for the development of information support for professional activity and professional communication. An important component of the information support of archival activity in the period of information technologies development is the presentation of the product on the Internet using its own website. This is providing the user with access to archival documents through information bases and reading rooms, providing as complete and objective information as possible about the composition and content of archival funds through the global Internet network. The purpose of the article. To conduct a study of the application of innovative technologies in the practical activity of archival institutions and the improvement of its information support. The methodology. The article examines the need to modernize the archive file by implementing a website into the activities of these institutions. The results. As a result, the needs of users were determined and a website project was developed, which will provide users with the necessary services and improve the prestige of the institution. The scientific novelty. The article highlights innovative ideas for creating a web portal for the archive that will cover all the necessary services. The practical significance. The practically implemented website project for the archive of the Lviv Polytechnic can be used by default to present its services on the Internet, communicate with citizens, as well as provide services through the created functions of submitting and receiving documents.